Central pontine myelinolysis associated with hypokalaemia in anorexia nervosa. Issue 3 (1st March 2003) - Sugimoto, T; Murata, T; Omori, M; Wada, Y
Abstract : A 31 year old man was admitted to hospital with of anorexia, binge eating, and self induced vomiting. On admission, he showed a pronounced low weight and disturbance of the body image and was diagnosed as having anorexia nervosa. In addition, electrolyte abnormalities, mainly hypokalaemia, and increased serum renin and aldosterone concentrations were recorded, suggesting pseudo-Bartter syndrome as a complication. Under frequent monitoring of the serum potassium and sodium concentrations, serum electrolytes were gradually corrected, but brain magnetic resonance imaging revealed reversible central pontine myelinolysis (CPM). Although attention has been mainly paid to the association of CPM with rapid correction of hyponatraemia and abnormal osmolality, this case report strongly suggested the involvement of hypokalaemia in the pathogenesis of CPM.